Synergetic effects of 5-aminolevulinic acid and Ascophyllum nodosum seaweed extracts on Asparagus phenolics and stress related genes under saline irrigation - Al-Ghamdi, Abdullah A (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.